2012
DOI: 10.4236/jwarp.2012.411110
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeophysical Parameters Estimation for Aquifer Characterisation in Hard Rock Environment: A Case Study from Yaounde, Cameroon

Abstract: Detailed local geological and hydrogeophysical investigations were carried out for the aquifer in Yaoundé, Cameroon to delineate the architecture of different subsurface geological horizons using lithologs and generated vertical electrical sounding (VES) data. An attempt has also been made to estimate aquifer transmissivity from resistivity data. The transmissivity of the uncon?ned aquifer was computed by determining the Dar-Zarrouk parameters (longitudinal unit conductance and transverse unit resistance) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…From field observations, borehole lithostratigraphic sections and by comparing various case studies in similar terrain in gneiss-type rocks and in some parts of Yaoundé have indicated that topography controls groundwater flow and that base flow to rivers is an important factor moderating groundwater movement in Yaoundé as shown here by the groundwater contours for four seasons (Teikeu et al, 2016;Wyns et al, 2004;Clark, 1985;Acworth, 1987;Obiefuna & Sheriff, 2011;Fouépé Takounjou et al, 2012). Lithologies from their VES curves corroborated the lithologs of boreholes from this area (Teikeu et al, 2012). Some researchers have concluded with a dual aquifer conceptual model for fractured rock gneiss aquifers (Teikeu et al, 2012;Wyns et al, 2004).…”
Section: Aquifer Settingmentioning
confidence: 56%
See 2 more Smart Citations
“…From field observations, borehole lithostratigraphic sections and by comparing various case studies in similar terrain in gneiss-type rocks and in some parts of Yaoundé have indicated that topography controls groundwater flow and that base flow to rivers is an important factor moderating groundwater movement in Yaoundé as shown here by the groundwater contours for four seasons (Teikeu et al, 2016;Wyns et al, 2004;Clark, 1985;Acworth, 1987;Obiefuna & Sheriff, 2011;Fouépé Takounjou et al, 2012). Lithologies from their VES curves corroborated the lithologs of boreholes from this area (Teikeu et al, 2012). Some researchers have concluded with a dual aquifer conceptual model for fractured rock gneiss aquifers (Teikeu et al, 2012;Wyns et al, 2004).…”
Section: Aquifer Settingmentioning
confidence: 56%
“…Lithologies from their VES curves corroborated the lithologs of boreholes from this area (Teikeu et al, 2012). Some researchers have concluded with a dual aquifer conceptual model for fractured rock gneiss aquifers (Teikeu et al, 2012;Wyns et al, 2004). Although weathered gneiss terrains are layered, aquifer models suitable for sedimentary terrains of layered formations cannot apply here where the fissures and fractures cut across the layering in the formations' regolith that still retain relics of the continuous gneiss fractures and fissures intact in saprolite, weathered basement and fresh fractured basement.…”
Section: Aquifer Settingmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, Kazakis et al [12] obtained linear relations between the K and the resistivity of the aquifer. Some authors have found a linear relationship between T and T R [16][17][18][19]. The works of these authors suggest that there is a relation between the transmissivity of an aquifer and the parameter of Dar-Zarouk, also that this relation is influenced by the geo-hydrological conditions of the place and maintains an exponential relation.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we are experimenting in the search for exponential relations between R o and R w ; T and K with the electric transverse resistance. The transverse resistance is one of the Dar-Zarrouk parameters and has been proved to be useful in the evaluation of hydraulic conductivity and transmissivity [14][15][16][17][18][19][20]. In a flat and stratified earth model, each geoelectric layer is characterized by a thickness h and an electrical resistivity ρ.…”
Section: Introductionmentioning
confidence: 99%